Typology of Scientists for Strengthening and Innovating Education in al-Jami' al-Musnad as-Shahih al-Muhtashar min Umuri Rasulullah Shalallahu 'Alaihi Wasallama wa Sunanihi wa Ayyamihi - Fadhlurrahman; Muh. Alif Kurniawan; Abdulnassir Yassin; Agus Martins; Windi Dwi Astuti; Lathifah Irsyadiyah Husna; Sefi Fifit Fardana; Khofifah Tulmufida Uba; Eko Setyo Wiyanto (STAI Terpadu Yogyakarta, 2024)
Scientists are people who are experts or have a lot of knowledge about science and even people who are involved in the field of science. In law (UU) number: 8 TAHUN 1990 (8/1990), concerning: Indonesian Science Chapter 1 article 1 paragraph 2 states that Scientists are people who explore, master, develop, and apply science and/or technology for the sake of seeking truth and improving welfare, dignity, and human dignity. Islamic scientists were very influential in the development of scientific development in the West. This research is literature research (literature study) by looking for various kinds of primary data sources about the concept of scientists to strengthen and innovate education that can be integrated-interconnected into the principles that are the basis of Islamic Religious Education for scientists. The research resulted in the concept of scientists in the book al-jami' al-musnad as-shahih al-muhtashar min umuri rasulullah shalallahu 'alaihi wasallama wa sunanihi wa ayyamihi. The fundamental attitudes and traits for scientists are found that a scientist must have the attitude and traits of discipline and honesty and master the knowledge in his field. This research has novelty taken from the book